Doping and compensation in Al-rich AlGaN grown on single crystal AlN and sapphire by MOCVD - Bryan, Isaac; Bryan, Zachary; Washiyama, Shun; Reddy, Pramod; Gaddy, Benjamin; Sarkar, Biplab; Breckenridge, M. Hayden; Guo, Qiang; Bobea, Milena; Tweedie, James; Mita, Seiji; Irving, Douglas; et al. (Applied physics letters, 2018)
In order to understand the influence of dislocations on doping and compensation in Al-rich AlGaN, thin films were grown by metal organic chemical vapor deposition (MOCVD) on different templates on sapphire and low dislocation density single crystalline AlN. AlGaN grown on AlN exhibited the highest conductivity, carrier concentration, and mobility for any doping concentration due to low threading dislocation related compensation and reduced self-compensation. The onset of self-compensation, i.e., the “knee behavior” in conductivity, was found to depend only on the chemical potential of silicon, strongly indicating the cation vacancy complex with Si as the source of self-compensation. However, the magnitude of self-compensation was found to increase with an increase in dislocation density, and consequently, AlGaN grown on AlN substrates demonstrated higher conductivity over the entire doping range.